Bergamot (Citrus bergamia Risso) as a source of nutraceuticals: Limonoids and flavonoids. (January 2016) - Russo, Marina; Arigò, Adriana; Calabrò, Maria Luisa; Farnetti, Sara; Mondello, Luigi; Dugo, Paola
Highlights: Limonoids were determined in bergamot fruits for the first time. Limonoid aglycones are the more abundant in seeds and peels. Significant amounts of limonoid were purified by means of preparative HPLC HPLC/PDA/MS from bergamot seeds and juice. Abstract: Limonoids are human health promoters, and have many pharmacological properties: anticancer, antioxidant, antibacterial and antifungal. To the best of the authors' knowledge, there are no previous reports on the composition of limonoids in bergamot fruits, so the aim of this work was to characterize bergamot peel, pulp, seed and juice. Samples analysed showed the presence of both limonoids aglycones and glucosides. Limonoid aglycones are the most abundant in seeds and peels (70 and 80% of the total, respectively), while limonoid glucosides are the more abundant in juices and pulps (61 and 76% of the total, respectively). Moreover a method to isolate pure limonoids from bergamot seeds and juice by means of a 2D-HPLC/PDA/MS preparative system is proposed. Pure molecules isolated were used to build calibration curves to quantify limonoids in real samples. Isolation of nutraceuticals from seeds and juices can represent an advantageous way to re-evaluate these by-products.